Pergeseran Minat Masyarakat untuk Menyekolahkan Anak di Sekolah Dasar Islam Terpadu (SDIT) di Kota Serang - Shilfa Muhimatun Ulwiyah; Desty Endrawati Subroto; Cika Nuralifa; Rizka Mutiara; Faikoh Faikoh (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Many parents are not interested in enrolling their children in Integrated Islamic Elementary Schools (SDIT), particularly in the Pulo Ampel and Kadumerak Districts of Serang City. One of the main contributing factors to this issue is the parents’ economic condition, especially when compared to the affordability of public elementary schools. The lack of enthusiasm among parents toward SDITs, in contrast to public schools, forms the basis of this research. This study employs a qualitative research strategy with a specific research design. The researcher selected a sample of thirty (30) informants using purposive sampling, with the research subjects being parents of school-age children. Data collection tools included observation sheets and questionnaires, and information was gathered through in-depth interviews, systematic observation, and detailed documentation. The data analysis followed the steps outlined by Miles and Huberman: (1) data collection, (2) data reduction, (3) data display, and (4) drawing conclusions. Triangulation and related methods were used to ensure the accuracy of the data. The results showed that 70% of parents from Kadumerak District and 60% from Pulo Ampel District did not choose SDIT due to the high cost of tuition. The primary factor discouraging parents from enrolling their children in SDIT was the mismatch between school fees and the parents’ financial capacity. Additionally, the intensive school schedule often led to student fatigue and reduced time for other activities.